Utilization of carrot residue in macaroons - Miranda, Eliza Diamante R.
With the accumulation of wastes, recycling has become inevitable. In line with this, it is very practical to utilize carrot residue obtained after carrot juice extraction for other food preparations. Residue recovery of carrots was measured to be 40.5% after juice extraction. This residue was then dried at 60°C at three different drying times to produce carrot residue flakes. Acceptability of the product was based on the results of the sensory evaluation and moisture content. The chosen product was then utilized to determine the optimum level of carrot residue flakes to be substituted in macaroons -- 25, 50 and 75%. Three more production batches of the chosen level of substitution was performed and subjected to sensory evaluation to test for reproducibility. The standardized carrot residue macaroon was then subjected to proximate analysis and vitamin A analysis. Results revealed that a drying time of 150 minutes at 60°C produced the most accepted carrot residue flakes based on moisture analysis and sensory evaluation. This was used as substitute for desiccated coconut in macaroons wherein 75% level of substitution was considered to be the best. Standardization of the chosen level showed no significant difference when subjected to statistical analysis using ANOVA. Results of the chemical analysis on wet basis revealed that carrot residue macaroon contained 25.73% moisture, 54.92% carbohydrates, 5.48% crude fat, 11.34% crude protein, 1.52% crude fiber and 1.01% ash. It also contains 75.23 RE of vitamin A which is about 18.18% of a child's RDA.